E.T. the Extra Terrestrial - Spielberg, Steven; Universal Pictures ([s.l.] Universal Pictures, 2002)
E.T. and his fellow space travelers come peacefully to Earth to gather plants in a misty redwood forest. When they are discovered by Elliot, a ten-year old boy with whom he develops a friendships and love.
VCD
Written by Melissa Mathison, produced by Steven Spielberg & Kathleen Kennedy ; directed by Steven Spielberg
Drew Barrymore, Henry Thomas
Keywords: Fantasy; Science fiction